No Tempest in a Teacup: Fentanyl Trafficking as a Threat to United States’ Security and Its Geopolitical Implications - Manullang, Abel Josafat; Sudrajat, Jasson Aditya; Natawibawa, Ibrahim Izzan (Security Intelligence Terrorism Journal (SITJ), 2025)
Drug trafficking is one of globalization's rotten fruits that the United States (US) has struggled against as it has witnessed 4 waves of opioid epidemic. Chief among the trafficked drugs is fentanyl that caused more than 100.000 in the last two years. Its crossboundary nature, how they originate from outside the US, makes it intricate to solve as it would require a holistic approach. Against that backdrop, this study seeks to provide a security understanding of the issue and its geopolitical repercussions for the US. The writers employ the qualitative research method that entails the use of both primary and secondary data procured from the internet. The article begins with an elaboration of how fentanyl trafficking poses a threat to the security of the US. Here, fentanyl trafficking falls under the non-traditional threat with a far-reaching security implication, especially in the national and human sense. Following that, the geopolitical repercussions of this transnational threat is discussed. Among them is how the issue has riled up the US relations with Mexico and China. Finally, an overview of the existing means to deal with the problem is provided along with some suggestions as to the path ahead.